Digital solutions for municipal differentiation of sustainable development in the subject of Russia - Sidorov, Alexander; Vasilieva, Darya; Kholopov, Yuriy; Tsekoeva, Fatima (E3S web of conferences, 2021)
Using digital technology the municipal differentiation of sustainable development of the subject of Russia - the Samara region - was investigated. The rating of municipal districts according to the digital data of environmental sustainability was compiled. The most favorable environmental environment was characterized by the districts geographically located on the periphery of the region regardless of natural and climatic conditions. Environmental risks and threats to sustainable development developed in the municipal territories adjacent to large urban agglomerations. The authors analyzed the medium-term strategies for sustainable development of the region's municipalities. These documents revealed a significant difference in the number of environmental objectives, which sometimes do not coincide with the real situation. A typology of districts by the number of planned environmental sustainability programs was compiled. In order to reduce municipal differentiation, it was proposed to implement the provisions of state federal, regional and municipal programs of sustainable development in the corresponding territories, taking into account municipal characteristics.